Knowledge and beliefs on breast cancer screening and uptake among Yemeni female school teachers in Malaysia - Sarah Noman; Nadya Mohamed Elfeturi Elarusy; Hejar Abdul Rahman; Suriani Ismail; Meram Azzani; Khalda Mohamed Khamis; Musheer A. Aljaberi (Scientific Reports)
Abstract Limited breast cancer screening uptake among women may lead to late-stage diagnosis and reduce the survival rate. Hence, this study was conducted to determine breast cancer screening (BCS) uptake and its association with knowledge, beliefs, and socio-demographic factors among female Yemeni school teachers in Malaysia. A cross-sectional study was conducted as part of a large cluster-randomized controlled trial (CRT) among 180 Yemeni female teachers aged 20 years and above. The sample was selected using cluster sampling from 12 Arabic schools in the Klang Valley area, Malaysia. Data was collected using a validated Arabic questionnaire. Data analysis was performed using the SPSS 22.0 software. Both descriptive and logistic regression analyses were employed. The logit model with a p-value less than 0.05 was conducted to determine the predictors of BCS uptake. The screening uptake by the study participants was 23.3% (n = 42), 21.1% (n = 38), and 5.6% (n = 10) for breast self-examination (BSE), clinical breast examination (CBE) and mammogram (MMG), respectively. Additionally, the total mean knowledge score was 18.02 (SD = 5.82). Regarding the participants’ beliefs, the mean benefits and mean barriers of BSE were 23.29 (SD = 3.77), and 12.97 (SD = 3.80), respectively. In addition, mean confidence in doing BSE and mean health motivation were 31.85 (SD = 7.17) and 27.95 (SD = 4.22), respectively. Besides, the mean benefits of MMG were 21.26 (SD = 4.07), and the mean barriers to MMG were 14.81 (SD = 2.14). The logit model showed that higher knowledge among study participants increased the probability of performing BSE, CBE, and MMG with (OR = 1.09, 95% CI 1.01–1.17, p = 0.021), (OR = 1.08, 95% CI 1.00–1.16, p = 0.036), and (OR = 1.47, 95% CI: 1.14–1.91, p = 0.003), respectively. In addition, the higher confidence level increased the probability of performing BSE (OR = 1.090, 95% CI 1.017–1.168, p = 0.014). However, more barriers to CBE were associated with a decrease in the probability of performing CBE (OR = 0.892, 95% CI 0.802–0.992, p = 0.034). Moreover, as the participants got older, the MMG uptake increased (OR = 1.418, 95% CI 1.116–1.801, p = 0.004). Breast cancer screening uptake and knowledge, as well as beliefs concerning BCS are low among Yemeni school teachers in Malaysia. Conducting educational interventions on BCS is needed to improve awareness and encourage early detection of BC among women.